Pengembangan Karier Guru Di Pesantren Darul Ihsan Hamparan Perak Deli Serdang - Agus Salim Salabi (Pusdikra Publishing, 2021)
Career development is the process of identifying the employee's career potential and material and applying the right ways to develop this potential. The teacher career development process at Pesantrren Darul Ihsan begins with the implementation of monitoring and evaluation of teacher performance. This study aims to analyze and find: 1) the concept of teacher career development at Pesantren Darul Ihsan Hamparan Perak Deli Serdang, and 2) the types of teacher career development at Pesantren Darul Ihsan Hamparan Perak Deli Serdang. The two focuses are studied with the theoretical approach of career management, human resource management, and human resource development as well as several other relevant theories. This study uses a qualitative research model with a case study approach. The data collection technique is by using semi-structured interviews and document studies. Furthermore, after the data has been collected, it is analyzed using several steps: data condensation, data display and conclusion, drawing and verification. The results of this study: 1) Teacher career development is carried out in the form of a personal and career advancement plan, as well as monitoring and evaluation which have implications for: (a) repositioning, (b) dismissal, c) resignation, d) retire. 2) Types of teacher career development that are: short courses, study assignments or study permit, and in house training (IHT). Meanwhile, pesantren support for the career development of teachers is conditional and unconditional.